Clinical Presentation of Acute Hepatic Failure - A Study of 40 Cases - Islam, N; Zaman, A; Abdullah, ABM (Bangladesh Medical Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Acute hepatic failure (ALF) is a medical emergency. The clinical presentation of acute liver failure depends upon the causes. A total 40 patients of ALF were observed for clinical presentation during the period from January 2003 to July 2004. The patients were admitted in three different tertiary care hospitals in Bangladesh. The patients were selected randomly by the diagnostic criteria. Male predominant majority of the patients were between the age 10 - 40 years & presented within the 4th week of illness. Patients presented with jaundice and varying grades of hepatic encepalopathy. Most of the patients presented with nausea, Vomiting and loss of appetite. About a quarter patients presented with bleeding manifestation. About half of the patients presented with fever but itching & ascites were the least presenting features in this study. DOI: 10.3329/bmj.v36i2.3607 Bangladesh Medical Journal 36(2) 2007 31-33